The Influence of Teaching Practices on the Ability to Recognize Field Schooling of Economics Education Students of FKIP, University of Riau - Ardelia Naisya Agustina; Hendripides Hendripides; Hardisem Syabrus (CV. Rayyan Dwi Bharata, 2023)
When participating in PLP activities, students must be able to apply basic teaching skills. However, in reality the basic skills of teaching economics education students class of 2019 are relatively low, this can be seen from the final grades of teaching practice courses. This study aims to determine whether there is a positive and significant influence between teaching practices on the PLP abilities of Economics Education students class of 2019 FKIP, University of Riau. This research was conducted at the Economics Education Study Program, FKIP, University of Riau. This research method is descriptive quantitative. The data collection technique used was documentation using the final grades of PLP courses and teaching practices. The results showed that teaching practices had a positive and significant effect on the ability to recognize the field of schooling for Economics Education students class of 2019, FKIP, University of Riau. This means that the better the value of teaching practice, the better the PLP ability of Economics Education students class of 2019 FKIP, University of Riau